The Crucial Importance of Typical Discussion Roles of Pupils for the Effective Implementation of Peer Instruction in Teaching Elemantary School Mathematics - Zadražil, Tomáš (Scientia in educatione, 2021)
Studies over the past decade have indicated that Czech pupils do not have an appropriate level of mathematics comprehension and their attitudes towards this subject deteriorate over time. The article deals with a possible solution to the described problem; namely the implementation of peer instruction, an active learning strategy, in elementary mathematics teaching. In order to decide whether it is possible to use peer instruction as a teaching method in an elementary school environment, action research project with the properties of a mixed empirical study was performed in one eighth grade class (thirty participants) at a Czech multi-year grammar school. The main idea was to compare the results of the class before, during, and after the implementation of peer instruction. The pupils’ level of understanding was monitored by normalized learning gains calculated on the basis of pre/post-testing design. Changes in the pupils’ attitudes towards mathematics were mapped using continuous and pre/post-test questionnaires. In the spirit of the action research, interim data and results were regularly discussed with a group of selected pupils or experts in the field. The results show that there is a strong relationship between normalized learning gain and one of four typical roles with which pupils identify during group discussions: passengers, standard discussants, advisors, and dominant speakers. The research has also indicated that peer instruction needs to be appropriately modified to increase the passengers’ activity.